Pandangan tentang keselamatanahl al-kitab dalam tafsir al-maraghiThe Concept of Salvation for ahl al-kitab in the - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
ABSTRACT The main aim of the research is to review al-Maraghi's interpretations of the all' al-kitiib and its salvations. The model of research is library research. Then, the abundant data was collected from Tafsir al-Maraghi, especially his interpretations related to the topic. All of the data were collected by using Qur'anic concordance. The versus are collected by refering to words or phrases which indicates to the conditions, appreciations, and salvation of ahl al-kith'''. Then they will be classified according to the content and al-Maraghi's interpretations. The primary result of the research is that, according to al-Maraghi, basically all of the ahl al-kita communities will get salvation if they have "surrender to the will of God" or have islam (in its general meaning). However, in another side of his exegeses, he also emphasizes that the salvation for them must be restricted to believe in Muhammad. In other word, in order to get salvation they need to convert as Moslem first. Actually, this kind of doctrine, according to al-Maraghi, has been written down in its own sacred texts, but is corrupted by the writers or the scholars since the first time. Finally, it is worth nothing that most of al-Maraghi's exegeses about the salvation of ahl al-kitiib are inclusive ones, This can be proved by the fact that most of his interpretations tend to appreciate their spirituality and belief.